1979
DOI: 10.3758/bf03329409
|View full text |Cite
|
Sign up to set email alerts
|

Learning and retention of sucrose taste aversion in weanling rats

Abstract: Sixty rat pups, 21 days old, drank 9% sucrose and then received a single injection of distilled water or .3, .6, 1.8, or 3.0 mEq of lithium chloride (LiCI). Testing with a two-bottle choice procedure showed that sucrose taste aversion occurred reliably following injections of 1.8 and 3.0 mEq of LiCI, but not following .3-or .6·mEq injections. In Experiment 2, 80 rat pups, 21 days old, drank 9% sucrose and received an injection of LiCI (3.0 mEq) or distilled water and then were tested for taste aversion 24, 48,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…However, it would be amistake to emphasize a particular age range as critical, in an absolute sense, for the development of latent inhibition, because parametric and other methodological factors are likely to have a large effect on the point in ontogeny when this phenomenon can first be demonstrated. For example, more stimu-lus preexposure might cause latent inhibition to appear earlier in development, and indeed one study that employed eight preexposures to the CS (twice the number in the present one) showed significant latent inhibition of taste-aversion learning in rats at 20-25 days of age (Franchina et al, 1980). More recently, interference with conditioning by taste preexposure has been provisionally reported in 12-day-old rats by Kraemer, Hoffman, and Spear (1988).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, it would be amistake to emphasize a particular age range as critical, in an absolute sense, for the development of latent inhibition, because parametric and other methodological factors are likely to have a large effect on the point in ontogeny when this phenomenon can first be demonstrated. For example, more stimu-lus preexposure might cause latent inhibition to appear earlier in development, and indeed one study that employed eight preexposures to the CS (twice the number in the present one) showed significant latent inhibition of taste-aversion learning in rats at 20-25 days of age (Franchina et al, 1980). More recently, interference with conditioning by taste preexposure has been provisionally reported in 12-day-old rats by Kraemer, Hoffman, and Spear (1988).…”
Section: Discussionsupporting
confidence: 50%
“…Previous developmental studies of latent inhibition in taste-aversion learning have tended to focus on the weanling period or to compare weanling rats and adults (Franchina et al, 1980;Klein et al, 1977;Misanin et al, 1983). In the first experiment, we sought to test several age groups over a narrower age range under the same experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may indeed be that hippocampal functioning is involved in the age-related expression of LI, but it is also clear that the behavioral evidence is equivocal. Studies of aversive conditioning have shown that conditioned reactions to odors and tastes can be reduced by nonreinforced preexposure to these stimuli (Franchina, Domato, Patsiokas, & Griesemer, 1980;Hoffmann & Spear, 1989;Rudy & Cheatle, 1979). Perhaps LI with olfactory and gustatory stimuli involves a different mechanism from that involved in other forms oflearning, in which U has failed to appear in preweanlings, or perhaps differences in experimental parameters are crucial in determining whether or not LI will appear in immature rats.…”
mentioning
confidence: 99%
“…This conclusion does not imply that the neurological substrate for LI functions as well in preweanlings as it does in adults, nor that LI will be evident in immature rats with all kinds of learning procedures (seeKraemer et al, 1988; Nicolleet al, 1989). Rather, we suggest that we have discovered additional empirical evidence of a CSpreexposure effect in the immature rat, and that this and other evidence of LI in preweanling rats (e.g.,Franchina et al, 1980;Hoffmann & Spear, 1989;Kraemer et al, 1988;Rudy & Cheatle, 1979) is important both for the analysis of behavioral development and for understanding the biological basis oflearning and memory (see, e.g.,Nadel & Zola-Morgan, 1984;Nicolle et al, 1989;Sutherland & Rudy, 1989).…”
mentioning
confidence: 99%